PENGARUH TRANSISI POLITIK DI MYANMAR TERHADAP PENANGANAN PERDAGANGAN MANUSIA DI NEGARANYA - Wandansari, Riezqa Fitri; Utomo, Tri Cahyo; Wahyudi, Fendy Eko (Journal of International Relations, 2015)
Since 1962, the government of Myanmar had been controlled by themilitary power. This matter caused Myanmar people losing theirrights in social, political, and economic sectors. The losing of thoserights then became the factor of Myanmar people to do illegalmigration. However, the illegal migration that was done byMyanmar people make them became the victim of human trafficking.Myanmar even become the country with the highest number ofhuman trafficking victims in Mekong River region. In 2010,Myanmar did the election as a sign of the occurrence of politicaltransition there and became the end of the military power thatcontrolled the government for over 48 years. The purpose of theresearch is to know the effect of political transition in Myanmar onhandling human trafficking. This research is mainly based onGuillermo O’Donnell’s and Philippe C. Schmitter PoliticalTransition theory, stating that in times of political transition the shiftin human rights promotion occurs. Therefore, an idea arise in timesof Myanmar’s political transition, the number of human traffickingdeclines. Descriptive type is use on this research to explain thehuman trafficking phenomenon that happen when political transitionin Myanmar was on going. The result of this research shows thatpolitical transition in Myanmar take effect on the reduction of humantrafficking victim in Myanmar.